1982
DOI: 10.1182/blood.v59.3.455.455
|View full text |Cite
|
Sign up to set email alerts
|

The management of stage I--II Hodgkin's disease with irradiation alone or combined modality therapy: the Stanford experience

Abstract: At Stanford University, between 1968 and 1978, 230 patients with pathologic stage I--II Hodgkin's disease were treated on prospective clinical trials with either irradiation alone or irradiation followed by 6 cycles of adjuvant combination chemotherapy. The actuarial survival at 10 yr was 84% for patients in either treatment group. Freedom from relapse at 10 yr was 77% among patients treated with irradiation alone and 84% after treatment with combined modality therapy [p(Gehan) = 0.09]. Freedom from second rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Multivariate statistical methods have shown that mediastinal involvement is not an independent poor prognostic factor in most series (Cosset et al, 1984;Pillai et al, 1985;Sutcliffe et al, 1984;Tubiana et al, 1985;Horwich et al, 1986). In contrast, Hoppe et al (1982) report mediastinal bulk as a predictor of shorter disease-free survival but this did not account for the inferior outcome for females in our series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate statistical methods have shown that mediastinal involvement is not an independent poor prognostic factor in most series (Cosset et al, 1984;Pillai et al, 1985;Sutcliffe et al, 1984;Tubiana et al, 1985;Horwich et al, 1986). In contrast, Hoppe et al (1982) report mediastinal bulk as a predictor of shorter disease-free survival but this did not account for the inferior outcome for females in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Factors which predict the length of CR include B symptoms (Cosset et al, 1984;Tubiana et al, 1985;Longo et al, 1986), stage (Haybittle et al, 1985;Sutcliffe et al, 1984;Horwich et al, 1986), histology (Haybittle et al, 1985;Sutcliffe et al, 1984;Specht et al, 1987), number of disease sites (Cosset et al, 1984;Tubiana et al, 1985;Horwich et al, 1986), age (Sutcliffe et al, 1984;Tubiana et al, 1985;Longo et al, 1986), male sex (Tubiana et al, 1985;Specht et al, 1987), erythrocyte sedimentation rate (ESR) (Haybittle et al, 1985;Tubiana et al, 1985), tumour burden (Specht et al, 1987), number of extranodal sites (Longo et al, 1986), the presence of bulky mediastinal disease (Hoppe et al, 1982), time to achieve CR (Longo et al, 1986) and drug dose intensity (Pillai et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish these patients from the 60% or more of patients who will have some degree of mediastinal involvement at presentation [5,64], many discriminant functions were developed, but the one used most commonly is the mediastinal-thoracic (MT) Multani, Grossbard 43 ratio, a ratio between the largest transverse diameter of the mediastinal mass and the transverse diameter of the thorax at T5-6 on a standard standing postero-anterior chest radiograph [65]. Those patients with a ratio greater than 0.35, comprising 15%-20% of pathologic early stage patients [63,[65][66][67], have DFS rates ranging from 39%-55%, compared to 72%-92% for patients with smaller or no mediastinal involvement when treated with extended field (mantle and para-aortic fields) radiotherapy alone [38,[64][65][66][67][68][69][70][71][72][73][74][75]. Of note, most relapses in these patients are intrathoracic failures [38,[63][64][65][66][67][68]70].…”
Section: Clinical Management Of Early Stage Hodgkin's Diseasementioning
confidence: 99%
“…Those patients with a ratio greater than 0.35, comprising 15%-20% of pathologic early stage patients [63,[65][66][67], have DFS rates ranging from 39%-55%, compared to 72%-92% for patients with smaller or no mediastinal involvement when treated with extended field (mantle and para-aortic fields) radiotherapy alone [38,[64][65][66][67][68][69][70][71][72][73][74][75]. Of note, most relapses in these patients are intrathoracic failures [38,[63][64][65][66][67][68]70]. The addition of chemotherapy to the initial treatment regimen significantly decreases relapse risk, increasing the DFS rate from 73% to 92%.…”
Section: Clinical Management Of Early Stage Hodgkin's Diseasementioning
confidence: 99%
“…More recently, a separate group of 19 Stage I to I1 patients with large mediastinal disease received careful clinical staging followed by MOPP chemotherapy if there was no evidence of disease below the diaphragm. Mantle irradiation was given after the chemotherapy in all patients.…”
Section: Large Mediastinal Diseasementioning
confidence: 99%